Impact of diversified strategy, CEO’s compensation, the size of the Board of Commissioners,Frequency of the Board of Commissioners Meeting of Company Perform - Lutfi Refia Anandarin; Rina Trisnawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This StudyisAimed to Examine The InfluenceofDiversification Strategy,Chief Executive Officer'scompensation,Size of the Board of Commissioners, Meeting Frequency of Board of CommissioneronCompany Performance.The Proxies ofCompany PerformanceisReturn of Asset (ROA),The DIversification Strategy is Measured byHierschman Herfindah Index (HHI). Size of Board of the CommissionersIs Measured by the Numberof Board of Commissioners, And Meeting Frequency is Measured byThe Number of Meetings of the Board of Commissioners. The sampleis115 Companies Listed on LQ-45 Index IN Indonesia Stock Exchange During 2016-2019. THIS STUDY USES MULTILE MARGINAR LESPAR REGRESSION ANDUsing SPSS US Testing Tools. The Result of this Research Indicate that Diversification Strategy and Size of the Board of Commissioners Did Not Affout Company Perform Whitile TheChief Executive Officer's Company and Meeting Frequency of Board of Commissioner are significant positive effect to company performance. The Impact of Diversification Strategy does not Influence The Company Performance